Komunikasi Politik Berbasis Agama: Telaah Strategi Tuan Guru Dalam Politik di Lombok - Muhammad Amrillah (Kartika: Jurnal Studi Keislaman, 2025)
This article examines religion-based political communication strategies employed by Tuan Guru (Islamic religious leaders) in Lombok, a region predominantly inhabited by a devout society. As religious figures with both social and spiritual authority, Tuan Guru leverage their position to build political legitimacy through symbolic approaches, preaching (dakwah), and adaptation to digital technologies. This study uses a literature review method with a descriptive-analytical approach, focusing on the analysis of communication styles, religious narratives, religious symbols, and the media employed. The findings indicate that the political communication strategies of Tuan Guru are conveyed through the integration of moral values and Islamic teachings, structured systematically to influence voter behavior. Support from Tuan Guru is often perceived as a form of religious endorsement, thus having a significant electoral impact. However, such religious politicization also carries the risk of degrading the spiritual values and ethics of religious scholars if not guided with integrity. Therefore, it is essential to understand the dynamics of Tuan Guru's political communication in the context of social and technological changes to ensure their role remains relevant, transformative, and grounded in religious values